2010
DOI: 10.1590/s0103-90162010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, histochemistry and ultrastructure of seed and somatic embryo of Acrocomia aculeata (Arecaceae)

Abstract: Macaw palm (Acrocomia aculeata (Jacq.) Lodd. ex Mart.) is a tropical species with multiple uses, including oil supply for biodiesel production. However, structural and physiological studies of the seed are still scarce, as well as in vitro propagation techniques. The aim of this study was to characterize the anatomy, histochemistry and ultrastructure of the seed and the in vitro somatic embryo of A. aculeata, gaining insight into relationships between the post-harvest seed behavior and the somatic embryo conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 39 publications
10
66
0
2
Order By: Relevance
“…Starch likewise was not detected by histochemical tests in the embryos, nor in the in endosperm tissues of macaw palm seeds (Moura et al 2010). During early seedling development events (day 22 to 29) there was a considerable increase in starch content as opposed to lipid content, indicating the gluconeogenic origin of the polysaccharides.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Starch likewise was not detected by histochemical tests in the embryos, nor in the in endosperm tissues of macaw palm seeds (Moura et al 2010). During early seedling development events (day 22 to 29) there was a considerable increase in starch content as opposed to lipid content, indicating the gluconeogenic origin of the polysaccharides.…”
Section: Discussionmentioning
confidence: 79%
“…Gluconeogenesis is common in oilseeds, and is induced after visible germination (Graham 2008 (Oo & Stumpf 1983), Cocos nucifera (Sugimuma & Murakami 1990), and B. capitata (Oliveira et al 2013a). Because of the abundant mannose and galactose contents in the endosperm tissue, we assume that galactomannan is a storage compound for macaw palm seeds, and Moura et al (2010) suggested that the cell walls of macaw palm endosperm were composed of a type of mannan. Seed mannans and galactomannans are, in fact, important reserve compounds in the endosperm cell walls of many Arecaceae species because of this conversion into living sugars and possibly involvement in gluconeogenesis (Alang et al 1988;Buckeridge et al 2000;Buckeridge 2010).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, Moura et al (2010) found that somatic embryos had no proteins or lipids as storage compounds, which may be essential for conversion. Few somatic embryos progressed and failures occurred during their conversion into a plant, such as the failure of leaf primordium, or roots or both to develop or differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…Among them are anatomical and biochemical modifications, which allow seed tissues to survive through a period of anabiosis. For example, some recent studies have characterized the cell wall folding and ultrastructure of the cell containing fewer organelles as well as low vacuolated cells in vegetative tissues, such as the so-called orthodox seeds (Moura et al 2010) and also the resurrection plants (Moore et al 2008(Moore et al , 2009). However, considering desiccation sensitive seeds, adaptations on the cell wall or subcellular structure are impaired.…”
Section: The Anatomical and Biochemical Aspects Of Seed Maturationmentioning
confidence: 99%